Hospital Disaster Resilience in Indonesia: An Evidence-Based Synthesis of Flood and Earthquake Preparedness - Dicky Budiman; Tjahja Nurrobi (Poltekkes Kemenkes Surabaya, 2026)
Indonesia is one of the most disaster-prone countries in the world due to exposure to earthquakes, floods, tsunamis, volcanic eruptions, and climate-related hazards. Hospitals play a critical role in maintaining healthcare delivery during disasters, yet their resilience capacity varies. This study synthesized evidence on hospital disaster resilience in Indonesia, focusing on preparedness for flood and earthquake hazards. An evidence-based descriptive synthesis was conducted using peer-reviewed studies, national reports, policy documents, and international guidance. Findings were analyzed across four resilience domains the Hospital Safety Index: structural and non-structural safety, emergency management systems, continuity of essential services, and governance and policy integration. The review found that improvements in hospital resilience were most evident in governance, disaster management planning, and policy integration, largely driven by accreditation requirements and national disaster risk reduction initiatives. However, structural resilience remains insufficient in many facilities, particularly regarding seismic preparedness and non-structural mitigation measures. Flood preparedness is more advanced than earthquake preparedness because hydrometeorological hazards occur more frequently. Persistent vulnerabilities were identified in continuity of essential services, including electricity, water supply, sanitation systems, and healthcare waste management. Although disaster preparedness plans are increasingly available, operational readiness through emergency exercises remains inconsistent. Overall, hospital disaster resilience in Indonesia remains uneven, characterized by stronger administrative preparedness than infrastructural and functional resilience. Strengthening disaster-safe hospitals requires integrated resilience frameworks, climate-resilient health infrastructure, sustained investment in emergency preparedness, enhanced workforce capacity, and stronger implementation of disaster risk reduction policies across the healthcare system to ensure service continuity during future emergencies and disasters.